Studies on Schismatoglottideae (Araceae) of Borneo XXIII: Piptospatha colata and P. deceptrix, taxonomic novelties from Borneo - Boyce, P.C; Wong, Sin Yeng (Singapore Bulletin Garden, 2013)
Piptospatha colata P.C.Boyce & S.Y.Wong and P. deceptrix P.C.Boyce & S.Y.Wong are newly described, respectively from Kalimantan Barat and Kalimantan Utara, Indonesian Borneo. Recognition of these novelties takes to 13 the number of described, accepted species of Piptospatha. An updated key to the genus is provided and both species are illustrated, along with those species that are most similar.